Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Problem Based Learning di Sekolah Dasar - Yulianti, Efni; Astimar, Nelly (Universitas Negeri Padang, 2022)
Integrated thematic learning outcomes in elementary school are very low, to overcome these problems an effective approach is needed. This study aims to describe the improvement of integrated thematic learning outcomes using the Problem Based Learning (PBL) model at SDN Padang City. This type of research is Classroom Action Research (CAR). The subject of this study were the teacher and grade IVB students at SDN Padang City with a total of 33 people consisting of 17 men and 16 women. Data are analyzed using qualitative and quantitative approaches. This research was conducted in two cycles consisting of planning, implementation, observation and reflection. The results of this study are : in cycle 1 the average implementation of learning aspects of teachers is 82,14% and aspects of students are 78,56%. In cycle II the average implementation of learning aspects of teachers is 92,85% and students aspects are 92,85%. Cycle I student learning outcomes is 73 and cycle II student learning outcomes are 93. It can be concluded that by using Problem Based Learning (PBL) models can improve integrated thematic learning outcomes in SDN Padang City.